GACOR (Gastric Acid Detector): Inovasi Alat Pengukur Tingkat Asam Lambung - Taufan Maulana Putra; Dwiki Akmal Murad (Asian Journal of Innovation and Entrepreneurship, 2022)
GERD is a pathological condition in which gastric acid refluxes into the esophagus and causes symptoms. Various symptoms due to involvement of the esophagus, pharynx, larynx and airways. So that the symptoms experienced by patients will experience a burning sensation in the chest, difficulty swallowing, nausea, bad breath, complaining of heartburn and regurgitation. Usually, patients with GERD are diagnosed only through history taking, while the pH of gastric acid is not measured. There is also usually use an endoscopic examination to measure the pH of stomach acid. To overcome these problems, the need to solve the problem is to make a device that can measure the pH of stomach acid, not as expensive as an endoscopic examination, a non-invasive examination, and not necessarily with the help of medical personnel. Carrying easy use, using a pH sensor to detect salivary fluid. So we propose GACOR (Gastric Acid Detector): An Innovation of a pH Sensor-Based Gastric Acid Level Measuring Tool. Using this pH sensor later to measure salivary fluid, the pH sensor will detect the acidity value through an electronic ion exchange mechanism and measured oceans.